Pooled prevalence and determinants of household satisfaction with the community-based health insurance (CBHI) scheme in Ethiopia: a systematic review and meta-analysis - Getasew Berhanu; Yodit Abebe; Gizaw Sisay; Kassahun Animut (Cogent Public Health)
Since 2011, Ethiopia has implemented a community-based health insurance program to improve universal health coverage and promote access to health care by reducing health expenditures for low-income families. Various studies on household satisfaction with the CBHI scheme and its determinants have been undertaken in Ethiopia, and the results have been inconsistent across regions, with significant variability. However, no nationwide study assessed the pooled estimates to understand the inconsistencies and decision-making better. Therefore, this systematic review and meta-analysis aimed to determine the pooled prevalence of household satisfaction with the CBHI scheme in Ethiopia. Systematic review and meta-analysis were performed in compliance with PRISMA 2020 guidelines using a comprehensive search of PubMed/Medline, HINARI, SCOPUS, and Google scholar, supplemented by a manual search. The I2 test statistic was used to examine heterogeneity between studies. A random effects model estimated the overall prevalence of household satisfaction with the CBHI program. Of the 207 studies identified, five were included in this meta-analysis, and the overall pooled prevalence of household satisfaction with the CBHI scheme was 66.36% (95% CI 52.25%, 80.47%) in Ethiopia. Subgroup analysis showed a higher satisfaction rate of 67.55 (95% CI44.15, 90.95) in studies conducted in the Amhara region than in the SNNP region 65.94 (95% CI: 44.08, 87.8). Ethiopia’s pooled prevalence of household satisfaction with the CBHI program is moderate. Stakeholders involved in health service delivery must focus on dimensions of high service quality and enhance their knowledge of CBHI benefit packages through education and information campaigns.